The forensic evaluation of dental injuries in Istanbul, Turkey - (:unkn) unknown (ELSEVIER IRELAND LTD, 1999)
When a person is wounded in Turkey, he first attends hospital for treatment. The hospital is responsible for a report describing his injuries and their treatment and prognosis. The patient is then scanned by a specialist in forensic medicine who provides a final official report. In that report the lesions, the prognosis (including whether the injuries are life threatening or not) and the projected days away from daily activity are shown. In this study 18 317 cases which were examined in the second and the third Specialization Board of the Council of Forensic Medicine during 1996 were analyzed. Among them 112 cases were dental injuries. Dental injuries are reviewed according to their sex, causation, detail of injury, and they are compared to other studies. (C) 1999 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: forensic medicine; dental injuries; trauma score; TRAUMA; INCISORS